2012
DOI: 10.2527/jas.2011-4705
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of rectal temperature and peripheral temperature from implantable radio-frequency microchips in Holstein steers challenged with lipopolysaccharide under thermoneutral and high ambient temperatures1

Abstract: Early detection of disease can speed treatment, slow spread of disease in a herd, and improve health status of animals. Immune stimulation increases rectal temperature (RT). Injectable radio-frequency implants (RFI) can provide temperature at the site of implantation. The fidelity of peripheral site temperature, determined by RFI, relative to RT is unknown in cattle. We hypothesized that during lipopolysaccharide (LPS) challenge, temperature at 3 peripheral sites would be similar to RT in steers (n = 4; BW 77 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…In goats exposed to different environmental conditions, the temperature measured by microchips implanted at various body locations differed from core temperature (Torrao et al, 2011). Similar results are obtained in steers by Reid et al (2012), (Table 4). …”
Section: Temperature Measurement With Invasive Contact Sensorssupporting
confidence: 77%
“…In goats exposed to different environmental conditions, the temperature measured by microchips implanted at various body locations differed from core temperature (Torrao et al, 2011). Similar results are obtained in steers by Reid et al (2012), (Table 4). …”
Section: Temperature Measurement With Invasive Contact Sensorssupporting
confidence: 77%
“…EHEC strains are zoonotic pathogens that colonize the terminal rectums of cattle and other ruminants, where the normal temperature is approximately 39°C (42). It has also been demonstrated that the rectal temperature of cattle can rise to around 41°C when cattle are exposed to high ambient temperatures (43).…”
Section: Discussionmentioning
confidence: 99%
“…In general, measuring temperatures subcutaneously requires the use of implantable sensors and wireless transmission. The ST can vary among different implantation locations and many efforts have been made to determine the best locations for measuring accurate CBT in cattle [40,90,91]. Reid et al [91] used implantable radiofrequency identification (RFID) microchips measuring temperature in three sites, subcutaneously at the base of the ear, posterior to the poll, and beneath the umbilical fold.…”
Section: Subcutaneous Temperaturementioning
confidence: 99%
“…The ST can vary among different implantation locations and many efforts have been made to determine the best locations for measuring accurate CBT in cattle [40,90,91]. Reid et al [91] used implantable radiofrequency identification (RFID) microchips measuring temperature in three sites, subcutaneously at the base of the ear, posterior to the poll, and beneath the umbilical fold. They demonstrated that the temperatures at the base of the ear correlated most with RT with coefficients of 0.30 during heat stress and 0.20 during TNZ.…”
Section: Subcutaneous Temperaturementioning
confidence: 99%